Sister Wendy's story of painting the renaissance. ([London] BBC Video, 1996)
Sister Wendy Beckett explores the world of Renaissance painting.
VHS format.
Written & presented by Sister Wendy Beckett ; produced and directed by Tim Robinson ; a BBC production in association with WGBH/Boston.
Keywords: Painting, European; Painting, Renaissance